2021
DOI: 10.1038/s41598-021-83127-x
|View full text |Cite
|
Sign up to set email alerts
|

An elongated COI fragment to discriminate botryllid species and as an improved ascidian DNA barcode

Abstract: Botryllids are colonial ascidians widely studied for their potential invasiveness and as model organisms, however the morphological description and discrimination of these species is very problematic, leading to frequent specimen misidentifications. To facilitate species discrimination and detection of cryptic/new species, we developed new barcoding primers for the amplification of a COI fragment of about 860 bp (860-COI), which is an extension of the common Folmer's barcode region. Our 860-COI was successfull… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 87 publications
2
13
0
Order By: Relevance
“…The presence of two larger lateral tentacles given for B. anceps from Israel also confirms the genetic affinity regarding our assignment [27]. Besides a recent study, there is no recently reported record of B. jacksonianum [28]. The authors stated that B. jacksonianum which was synonymized with B. leachii by Kott [45, 46] is not accurate and essentially a distinct species.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The presence of two larger lateral tentacles given for B. anceps from Israel also confirms the genetic affinity regarding our assignment [27]. Besides a recent study, there is no recently reported record of B. jacksonianum [28]. The authors stated that B. jacksonianum which was synonymized with B. leachii by Kott [45, 46] is not accurate and essentially a distinct species.…”
Section: Discussionsupporting
confidence: 79%
“…This means barcoding of these animals is often not easy and can result in contamination. A new primer pair called 860-COI was designed to control for these issues [28, 47]. It provides sufficient resolution for the barcoding of botryllid ascidians even if they are cryptic or a new species.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we selected the mitochondrial cytochrome c oxidase subunit 1 (COI) for the detection of one-and two-toned color B. diegensis in South Korea. The COI was identified as the marker of choice for species discrimination [28] and has been effectively used for detecting NIS [8,29] and botryllids [27,30]. As a result, we recognized the presence of B. diegensis in South Korea based on DNA barcoding analysis.…”
Section: Discussionmentioning
confidence: 99%
“…as a Botrylloides sp .) due to the high similarities between the sister species of this taxon (Brunetti, 2009; Reem et al, 2018; Nydam et al, 2021; Salonna et al, 2021). Although the type of larval incubation and the structure of pyloric caecum have been reported to be support species differentiation (Brunetti, 2009), these features are very challenging to assess precisely during punctual field sampling.…”
Section: Discussionmentioning
confidence: 99%